2015
DOI: 10.1186/s12885-015-1477-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced caveolin-1 expression increases migration, anchorage-independent growth and invasion of endometrial adenocarcinoma cells

Abstract: BackgroundCaveolin-1 (CAV1) has been implicated both in tumor suppression and progression, whereby the specific role appears to be context dependent. Endometrial cancer is one of the most common malignancies of the female genital tract; however, little is known about the role of CAV1 in this disease.MethodsHere, we first determined by immunohistochemistry CAV1 protein levels in normal proliferative human endometrium and endometrial tumor samples. Then using two endometrial cancer cell lines (ECC: Ishikawa and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…33,35,36 Nevertheless, for several tumors CAV1 upregulation influences cancer cell survival and growth, favoring tumor progression (summarized in Table 1). [37][38][39] As an assumption, the prognostic value of CAV1 depends on cell specificity, cell transformation, tumor stage, the physiological context and most importantly on the nature of the tumor stroma. A loss of CAV1 in several tumor cells seems to induce a hyper-proliferative state, promoting cell proliferation, angiogenesis and tumor progression ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…33,35,36 Nevertheless, for several tumors CAV1 upregulation influences cancer cell survival and growth, favoring tumor progression (summarized in Table 1). [37][38][39] As an assumption, the prognostic value of CAV1 depends on cell specificity, cell transformation, tumor stage, the physiological context and most importantly on the nature of the tumor stroma. A loss of CAV1 in several tumor cells seems to induce a hyper-proliferative state, promoting cell proliferation, angiogenesis and tumor progression ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As documented in various studies, Cav-1 protein detected in different neoplasms has a complex and controversial role in cell proliferation, tumor development, and progression. 14,15 It has been also shown that Cav-1 expression decreases during development of breast, ovary, colon, and lung tumors. 14 Besides, re-expression of Cav-1 alters the transformed phenotype of mammary, colon and ovarian carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 It has been also shown that Cav-1 expression decreases during development of breast, ovary, colon, and lung tumors. 14 Besides, re-expression of Cav-1 alters the transformed phenotype of mammary, colon and ovarian carcinoma cells. [15][16][17] As a tumor suppressor protein Cav-1 promotes cell death possibly by blocking signaling pathways aberrantly activated in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…CAV-1 expression was evaluated by Real-time RT-PCR (Applied Biosystems StepOnePlus Real-time PCR system). The following primers were used (300 nM each): CAV-1 forward 5'-TGGTTTTACCGCTTGCTGTCTG-3', CAV-1 reverse 5'-GCAAGTTGATGCGGACATTGCT-3' (DIAZ-VALDIVIA et al 2015). The general conditions of experiment were the same as described by BUBKA et al (2014).…”
Section: Rt-pcrmentioning
confidence: 99%